Perilaku Ibu dalam Melakukan Perawatan Luka Sectio Caesarea di RS Inanta Kota Padangsidimpuan - Heriansyah, Rizka; Pebrianthy, Lola (Universitas Aufa Royhan, 2019)
The more complete the facilities and facilities provided by sectio caesarea are approved, the number of mothers who choose sectio caesarea to deliver their babies. This study discusses the post sectio caesarean mothers for the treatment of caesarean sectio injuries in Inanta Public Hospital Padangsidimpuan in 2018. This research method is descriptive with a large sample of 35 people. The study was conducted in August to December 2018. The instrument in this study consisted of a questionnaire of knowledge, attitudes and actions, each of which contained 10 questions. The results showed that most post sectio caesarean mothers have sufficient knowledge, namely 24 people (68.8%) and some who have good knowledge, 11 people (31.4%) and no mothers who have less knowledge. Based on attitude, post sectio caesarean mothers have a positive attitude of 35 people (100%). Based on the action, post sectio caesarare mothers performed wound care well with 35 people (100%). From the results of this study, it is expected to be beneficial for post sectio caesarean mothers, researchers, and hospitals to increase post sectio caesarean mothers for surgical wound care and increase the level of risk of sectio caesarean wound infection